(untitled) (Research, Society and Development, 2020)
Evaluation of the teaching of Orthodontics, in the graduation school in Dentistry of the Federal University of Campina Grande, in the formation of the general practitioner according to the proposals of the National Curricular Guidelines. An observational, cross-sectional and exploratory study was carried out through a questionnaire applied to 77 students from the 9th and 10th periods. For 64.9% of the students, the teaching methodologies used in the orthodontic discipline during graduation were considered very efficient for learning, but 58.4% considered it necessary to increase the time devoted to the discipline due to the extensive practical content of the same. (94.8%) feel capable to do the recovering of space by early loss of deciduous teeth and / or maintaining the space of loss until eruption of the permanent, (51.9%) consider themselves able to treat anterior open bite, in slow expansion of the maxilla (posterior crossbite) (33.8%) responded that they could treat and (32.5%) considered to be able to perform disjunction (rapid maxillary expansion) in all cases and (49.4%) in some cases. In more complex procedures in orthodontics, such as the correction of class III malocclusion with facial mask, only (11.7%) reported being able to perform such procedure. That the Orthodontics discipline of the undergraduate school in Dentistry of the UFCG contributes satisfactorily in the training of professionals able to perform preventive and interceptive orthodontic procedures required by the demands of a generalist in the private sphere and / or public according to the DCN, requiring only more time in the curriculum to provide them with greater autonomy in performing more complex orthodontic procedures.